The Effect of Competence and Career Development on Employee Interest in Certain Functional Positions with Compensation as Intervening Variable - Veranita Veranita; Dedi Purwana; Ari Saptono (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2022)
The problem that occurs are there is lack of still ASN to understanding about JFT, and the formation of ASN placement is still not in accordance with JFT competencies. The purpose of this study is to determine the effect of competence on the interest of employees at JFT, Career Development influences the interest of JFT employees, the effect of competence on compensation. The study was quantitative research , the data collection methods are documentation and questionnaires. Data analysis used Partial Least Square (PLS), the samples of this research are Secretariat General Employees of the Ministry of Religion of the Republic of Indonesia. The results of the research show that competence has a positive effect on employee interest, career development has a positive effect on employee interest, competence has a positive effect on competence has a positive effect on compensation for employees of the Secretariat General of the Ministry of Religion of the Republic of Indonesia Keywords: Career Development, Compensation, Employee Interest